PEMBUATAN NANOKOMPOSIT POLIVINIL ALKOHOL/NANOSERAT SELULOSA YANG DIISOLASI DARI TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jack) DENGAN METODE LEDAK UAP - Dwi Indria Cherlina; Saharman Gea; Hamonangan Nainggolan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
The manufacture of nanocomposites polyvinyl alcohol/cellulose nanofiber isolated from empty bunch fruit palm oil has been done. The isolation process was carried out in two stages : α-cellulose from EBFPO which followed by isolation of CN from α-cellulose using steam explosion method. The process of α-cellulose hydrolisis was done using H2C2O4 11%. Nanocomposites PVA/CN were characterized by morphologycal, thermal, and mechanical analysis. FT-IR spectra show C-O-C stretch of cellulose nanofiber at 1059,99 cm-1, which indicated that there are glycoside bonding in coumpound structure. The peaks near 2900,94 cm-1 and 3348,42 cm-1 are representative of the C-H and OH groups. The result of transmission electron microscopy (TEM) image show that diameter of cellulose nanofibre around 44,6 nm. PVA/CN nanocomposites at the optimum ratio of (80:20)% showed the thermal stability around 263,48oC and tensile strength around 17,41 MPa and Young’s Modulus 0,9 GPa, and surface area was smooth and homogen.